Modeling the Effects of Interrelations Among External Support and Internal Factors on Teachers’ ICT Integration Ability in Less Developed Areas of China - Shun Xu; Tiehao Zhao; Zhongmei Zheng; Sha Zhu (SAGE Open)
The research exploring the cumulative impact of influencing factors on teachers’ ICT integration ability is lacking. Additionally, the mediating role of internal factors on the relationship between external support and teachers’ ICT integration ability has not been adequately addressed. This gap hinders the comprehensive enhancement of teachers’ ICT integration ability. This study administered a questionnaire survey involving 9,591 teachers from 238 primary and secondary schools across the Ningxia Hui Autonomous Region in China, and structural equation model was utilized to systematically examines the cumulative effects of external and internal factors on teachers’ ICT integration ability and the mediating role of internal factors on the relationship between external support and teachers’ ICT integration ability in less developed areas. The questionnaire consisted of scales measuring external support, professional development, internal motivation, positive attitude, and ICT integration ability. The results demonstrated that the positive impact of external support on teachers’ ICT integration ability can be significantly enhanced through the serial mediation effects of teachers’ professional development, intrinsic motivation, and a positive attitude towards ICT. Furthermore, it was established that teachers’ ICT integration ability can also be enhanced by providing ICT-related professional development when there is enough external support. These findings deepen the understanding of the effects of interrelations among external support and internal factors on teachers’ ICT integration ability in less developed areas, and could benefit the enhancement of teachers’ ICT integration ability. Practical implications for governments, schools, and teachers were also discussed.